2011
DOI: 10.1186/1471-2334-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Mycobacterium tuberculosis circulating in Kharkiv Oblast, Ukraine

Abstract: BackgroundA persistent increase of tuberculosis cases has recently been noted in the Ukraine. The reported incidence of drug-resistant isolates of M. tuberculosis is growing steadily; however, data on the genetic variation of isolates of M. tuberculosis circulating in northern Ukraine and on the spectrum and frequency of occurrence of mutations determining resistance to the principal anti-tuberculosis drugs isoniazid and rifampicin have not yet been reported.MethodsIsolates of M. tuberculosis from 98 tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
2
15
0
4
Order By: Relevance
“…Studies in Russia (54) and Ukraine (55) found that rpoB531 was highly prevalent in strains of the Beijing genotype. In contrast, we found no significant association between the genotype and any resistance-conferring mutation, including rpoB531.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Russia (54) and Ukraine (55) found that rpoB531 was highly prevalent in strains of the Beijing genotype. In contrast, we found no significant association between the genotype and any resistance-conferring mutation, including rpoB531.…”
Section: Discussionmentioning
confidence: 99%
“…В Республике Карелия на протяжении по-следнего десятилетия доля штаммов данного генотипа оставалась практически неизмен-ной (около 55%) [3]. В целом штаммы генотипа Beijing преобладают в структуре российской популяции M. tuberculosis (в среднем около 50%) и в странах постсоветского пространства: Бе-ларусь -36,2%, Украина -31,6%, Эстония -39,2% [7,15,20,25,28]. Напротив, в других странах Европы распространенность штаммов Beijing относительно невелика: Финляндия -5,2%, Швеция -5,8%, Польша -6,5%, причем их источники иные и более разнообразные, включая, в частности, штаммы, занесенные из Восточной Азии [6,11,24].…”
Section: материалы и методыunclassified
“…Так, если в Карелии и Ле-нинградской области их доля составляла 10,3% (что сопоставимо с Финляндией -7,3%), то в Псковской области превышала 20%, что близ-ко к показателю в Эстонии (17,8%) [1,3,18,24,25]. В Беларуси и Украине штаммы семейства LAM занимают второе место по распростра-ненности (около 23%) после Beijing и в структу-ре МЛУ штаммов (39,5 и 22,9% соответственно) [7,22,28].…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…The study showed that MDR-TB strains were actively transmitted in the northern Russia (Mäkinen et al, 2011). In Ukraine, where increase of TB cases is maintained, the number of drug-resistant isolates was reported to be growing steadily, and transmission of drug-resistant isolates seems to contribute to the spread of resistant TB (Dymova et al, 2011). The MDR-TB genotyping databases allow the comparison of M. tuberculosis strains to improve the application of appropriate public health actions at a national level and, ideally, it should be extended across country borders (Bifani et al, 2001;Gavin et al, 2011;Ritacco et al, 2011).…”
Section: Recent Transmission and Population Studiesmentioning
confidence: 99%